1992
DOI: 10.1073/pnas.89.12.5241
|View full text |Cite
|
Sign up to set email alerts
|

Restriction mapping of the genome of the protozoan parasite Theileria parva.

Abstract: We have used a modified linking clone strategy and pulsed-field gel electrophoresis to derive a map of the 29 Sfi I and 4 Not I sites in the 10 million base pawr genome of the protozoan parasite Theienaparva. This was achieved in the absence of classical genetic information. The map reveals four chromosomes. Several genes, including those for parasite antigens, have been located on the map, as has the single locus carrying the major repetitive sequence in this organism. The map forms the basis for a study of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Hybridization of the probe to S®I-digested, agarose embedded, T. parva DNA revealed that TpABC1 was located on the second largest (1258 kb) S®I fragment (Fig. 5B), which was consistent with hybridization to chromosome 1 according to the genomic restriction map (Morzaria and Young 1992). The TpABC2 sequence was also hybridized to blots of S®I digested T. parva DNA and (HMDRN and HMDRC), the mouse MHC-linked peptide transporter, HAM1, and the Escherichia coli haemolysin exporter protein, HlyB.…”
Section: Chromosomal Localization Of Tpabc1 and Tpabc2supporting
confidence: 69%
See 1 more Smart Citation
“…Hybridization of the probe to S®I-digested, agarose embedded, T. parva DNA revealed that TpABC1 was located on the second largest (1258 kb) S®I fragment (Fig. 5B), which was consistent with hybridization to chromosome 1 according to the genomic restriction map (Morzaria and Young 1992). The TpABC2 sequence was also hybridized to blots of S®I digested T. parva DNA and (HMDRN and HMDRC), the mouse MHC-linked peptide transporter, HAM1, and the Escherichia coli haemolysin exporter protein, HlyB.…”
Section: Chromosomal Localization Of Tpabc1 and Tpabc2supporting
confidence: 69%
“…It was thus of interest to determine the location of TpABC1 in the genome of T. parva. It has been shown that T. parva (Muguga) contains four chromosomes and 33 S®I fragments (Morzaria and Young 1992). Using the same conditions employed by Morzaria and Young (1992) to resolve the chromosomes of T. parva, the location of this gene was found to be on chromosome 1 of T. parva (Fig.…”
Section: Chromosomal Localization Of Tpabc1 and Tpabc2mentioning
confidence: 96%
“…The Tpr ORFs are tandemly arrayed within a single region of the T. parva genome. Previous analysis has shown that in T. parva Muguga the Tpr ORFs are present as a tandem array (3) and that the Tpr1 sequences are located on two adjacent, chromosome-internal, SfiI fragments (numbers 3 and 6) in the T. parva Muguga genome (34). In this study, a 115-bp sequence with 78% similarity to the extreme 3Ј end of the T. parva Muguga Tpr1 was identified 300 bp upstream of the large 624-and 656-codon ORFs in Uganda DNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The nucleotide sequence of the p67 sporozoite antigen gene (39), which is encoded on the same 780-kb SfiI fragment as the Tpr locus (34), is identical in T. parva Muguga, Boleni, and Uganda (40). The unusual conservation of the p67 gene, which extends to the 29-bp intron and the third base position of all codons, is in marked contrast to the exceptional divergence of the Tpr sequences.…”
Section: Discussionmentioning
confidence: 99%
“…To define the structural basis for these Morzaria and Young, 1992; Janse et al, 1992; variations, we have constructed full-length restriction Blaineau et al, 1991; Weiden et al, 1991). In Trypamaps of five chromosomes of 370 to 490 kb in Leish-nosoma brucei and Plasmodium falciparum, karyomania infantum clone LEM1317.…”
mentioning
confidence: 99%